"If We Want Things to Stay as They Are, Things Will Have to Change." Covid, Couture and the 1%. Issue 3 (23rd April 2021) - Faiers, Jonathan
Abstract: The current pandemic is demanding a radical reconceptualization of fashion. In the context of an unprecedented economic decline, the collapse of physical fashion retailing and a fundamental interrogation of previous clothing consumption patterns, can the same be said of haute couture luxury fashion? Taking the current couture season's promotional films as a starting point, this article discusses whether couture and its clientele has been forced to adapt or remains largely unaltered since couture's establishment in the nineteenth century and as represented in literature.